SINERGI LEMBAGA KURSUS DAN MASYARAKAT DALAM PENINGKATAN KOMPETENSI BAHASA INGGRIS ANAK DI BANJAR UMALAS KANGIN - Ni Komang Purwaningsih; Si Putu Agung Ayu Pertiwi Dewi (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2026)
English language acquisition from an early age is a crucial component in preparing young people to face challenges worldwide. However, limited access to good English language learning remains a problem in the community. This Community Service Program (PKM) aimed to improve the English skills of children in Banjar Umalas Kangin by collaborating with the community and a language course institution. The program involvds students from elementary to junior high school. The implementation method used an activity-based learning approach. During eight sessions, educational games, songs, stories, and role-playing were used. Speaking confidence and vocabulary mastery are measured during evaluations, which are conducted through observation and simple pre- and post-tests. The results of the activity indicated that the participating children had a desire to learn English, had a wider vocabulary, and were more confident. This activity demonstratds that the synergy between the community and the language course institution was beneficial in improving children's English learning in the banjar.